Usia, Paritas, Anemia Dengan Kejadian Perdarahan Post Partum - Yetty Dwi Fara; riona sanjaya (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
Postpartum hemorrhage is the leading cause of maternal mortality in low-income countries and the leading cause of nearly a quarter of all maternal deaths globally. Most of the deaths from postpartum hemorrhage occurred during the first 24 hours after discharge. Lampung Province experienced birth problems / complications by 19.2% with 2.6% of them being bleeding cases. This figure is higher than the national percentage of 2.4%. The purpose of this study was to determine the factors associated with the incidence of postpartum hemorrhage. Quantitative research design with cross sectional approach. The sample used the total population, namely all mothers giving birth in Cahaya Mas Village in 2019 totaling 33 people. The data was taken through the village of Cahaya Mas delivery report in 2019. The results of the study were obtained from 33 mothers who gave birth, 60.60% of mothers experienced bleeding, 66.67% were not risk parity, 69.70% were at no risk and 63.63% experienced anemia during pregnancy. Chi square test results showed that there was no relationship between age (p-value = 0.371), parity (p-value = 0.267) and anemia during pregnancy (p-value = 0.183).